Initial experience with the Solitaire X 3 mm stent retriever for the treatment of distal medium vessel occlusions - Ntoulias, Nikos; Brehm, Alex; Tsogkas, Ioannis; Jesser, Jessica; Caragliano, Antonio Armando; Demerath, Theo; van Es, A. C. G. M.; Gruber, Phillip; Vega, Pedro; Lüttich, Alex; Nayak, Sanjeev Kumar; Fandiño, Eduardo; et al. (Journal of Clinical Medicine, 2023)
Endovascular therapy (EVT) is the standard treatment for ischemic stroke caused by a large vessel occlusion (LVO). The effectiveness of EVT for distal medium vessel occlusions (MDVOs) is still uncertain, but newer, smaller devices show potential for EVT in MDVOs. The new Solitaire X 3 mm device offers a treatment option for MDVOs. Our study encompassed consecutive cases of primary and secondary MDVOs treated with the Solitaire X 3 mm stent-retriever as first-line EVT device between January and December 2022 at 12 European stroke centers. The primary endpoint was a first-pass near-complete or complete reperfusion, defined as a modified treatment in cerebral infarction (mTICI) score of 2c/3. Additionally, we examined reperfusion results, National Institutes of Health Stroke Scale (NIHSS) scores at 24 h and discharge, device malfunctions, complications and procedural technical parameters. Sixty-eight patients (38 women, mean age 72 ± 14 years) were included in our study. Median NIHSS at admission was 11 (IQR 6-16). In 53 (78%) cases, a primary combined approach was used as the frontline technique. Among all enrolled patients, first-pass mTICI 2c/3 was achieved in 22 (32%) and final mTICI 2c/3 in 46 (67.6%) patients after a median of 1.5 (IQR 1-2) passes. Final reperfusion mTICI 2b/3 was observed in 89.7% of our cases. We observed no device malfunctions. Median NIHSS at discharge was 2 (IQR 0-4), and no symptomatic intracranial hemorrhages were reported. Based on our analysis, the utilization of the Solitaire X 3 mm device appears to be both effective and safe for performing EVT in cases of MDVO stroke.